Impact of Demonetization on Indian Economy: A study on the effects of demonetization on the Indian economy (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Demonetization is the process of removing currency from general usage or circulation. In India’s case Government completely withdrawn the currency with the denomination of 1000. Along with 1000 currency notes 500 rupee notes were also withdrawn from circulation. For the old 500 currency notes new 500 rupee notes will be issued and a new currency note of 2000 denomination has been introduced in the economy. The present paper highlights the impact of demonetization on Indian economy.